THE EFFECT OF ONION (ALLIUM CEPA L.) ON HAIR HEALTH: BIOACTIVE PROPERTIES AND PRACTICAL APPLICATIONS - Kodirova Nargizakhon Umarovna (Modern American Journals, 2025)
This article analyzes the prostate cancer detection rate in different types of targeted transrectal biopsy. Early diagnosis of prostate cancer is a necessary condition for reducing mortality from this disease, since its detection at an early stage is often the only chance for cure. Currently, several options for targeted prostate biopsy have been proposed to facilitate early detection diseases.
Keywords: dopplerography, cognitive registration MRI, targeted biopsy, prostate cancer, glands, HistoScanning.